Participatory WebGIS Wisata Pulau Setokok - Farouki Dinda Rassarandi; Sudra Irawan; Oktavianto Gustin; Agung Riyadi; Muhammad Nashrullah; Nur Zahrati Janah; Afdhol Dzikri; Fadli Suandi; Rizki Widi Pratama; Destriani Kaban; Anindea Pramilaning Tyas; Fadiella Azhaara Ramadhanti; Cecep Maulana Hidayat (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
The Kelurahan of Setokok Island offers various tourist attractions with plenty of supporting facilities. In addition, Setokok Island, which is part of Batam City, has a very strategic position in the Sijori route, which contributes to the many visits by tourists, both local and international. However, all tourist objects on Setokok Island had not been managed properly. In addition, there is no complete information regarding the distribution of these attractions and the facilities they provide that can be accessed directly online. To address the potential and solve the problems, one of the actions that can be implemented to develop the tourism sector is a participatory mapping of tourist attractions and the facilities they provide in a complete, actual, and valid way in the kelurahan of Setokok Island. The results are then published in the form of WebGIS that can be accessed directly online so that more people will know all the tourism potential there. Hopefully, the local tourism sector in Setokok Island will develop and will directly improve the micro economy of the people of Setokok Island.